Composite copper foil and method for manufacturing the same and use thereof

CN117702114BActive Publication Date: 2026-11-03OMAT ADVANCED MATERIALS (GUANGDONG) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311469243.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-06
Publication Date
2026-11-03
Estimated Expiration
2043-11-06

AI Technical Summary

Technical Problem

Existing composite copper foils used in lithium batteries suffer from poor adhesion of the copper seed crystal layer, affecting performance and lifespan. Meanwhile, the NiCr polycrystalline alloy layer causes contamination of the electroplating solution, impacting the quality of the electroplated copper layer growth.

Method used

Amorphous thin films are used as metal modification layers, combined with the first copper layer and the base film, to improve the interfacial bonding energy, avoid the NiCr polycrystalline alloy layer, and improve the adhesion of the copper seed layer and the growth quality of the electroplated copper layer.

Benefits of technology

This improved the adhesion of the copper seed crystal layer and extended the service life of the electroplating solution, thereby enhancing the electrical performance and lifespan of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117702114B_ABST
    Figure CN117702114B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of battery materials, and particularly relates to a composite copper foil and a preparation method and application thereof. The composite copper foil comprises a base film, a metal modification layer, a first copper layer and a second copper layer which are sequentially arranged on the upper surface of the base film; the metal modification layer, the first copper layer and the second copper layer which are sequentially arranged on the lower surface of the base film; and the metal modification layer is an amorphous thin film layer. The amorphous thin film is used as the metal modification layer, which is combined with the first copper layer and the second copper layer, so that the square resistance of the composite copper foil is reduced, and the electrical performance is good; and the base film and the first copper layer, and the first copper layer and the amorphous thin film layer have good interface bonding energy, so that the service life of the composite copper foil is prolonged; in addition, since the NiCr polycrystalline alloy layer is not contained, the pollution of nickel to the electroplating solution is reduced, the growth quality of the second copper layer is improved, and the electrical performance of the composite copper foil is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials technology, and specifically relates to a composite copper foil, its preparation method, and its application. Background Technology

[0002] Compared to traditional batteries, lithium batteries offer advantages such as high energy density, long lifespan, light weight, and environmental friendliness, making them a promising candidate for the new energy vehicle lithium battery market. A lithium battery consists of a positive electrode current collector, positive electrode active material, separator, negative electrode active material, and negative electrode current collector. The battery converts chemical energy into electrical energy through the cyclic charging and discharging of the positive and negative electrode active materials. The positive and negative electrode current collectors are indispensable components of lithium batteries, collecting electrons generated by the positive and negative electrode active materials and outputting them to the external circuit, while simultaneously inputting electrons generated by the external circuit to the active material. Composite copper foil for lithium batteries is a novel current collector material with a "sandwich" structure. The middle layer consists of approximately 4.5μm thick polyethylene terephthalate (PET), polypropylene (PP), or polyimide (PI) film, with each outer layer plated with 1μm thick copper. Compared to the traditional 6μm thick lithium battery copper foil, composite copper foil offers advantages such as lower cost, higher safety, higher energy density, and longer lifespan. Therefore, composite copper foil replacing traditional copper foil has become the current trend in the development of lithium batteries.

[0003] However, in actual production, composite copper foil used to prepare lithium battery negative electrode current collectors is generally prepared by physical vapor deposition (PVD) and electroplating, sequentially forming a copper seed layer and an electroplated copper layer on the top and bottom surfaces of a PET base film. Due to the low surface energy of the PET and other polymer base film interfaces, the adhesion of the copper seed layer to the PET base film is poor, and the grain growth orientation is disordered, severely affecting the performance and lifespan of the composite copper foil. The traditional solution is to deposit a NiCr polycrystalline alloy layer on the base film as an adhesion layer. While this can improve adhesion, it also induces the growth orientation of the copper seed layer, affecting the growth quality of the electroplated copper layer. Furthermore, nickel contaminates the electroplating solution.

[0004] Therefore, there is an urgent need to provide a composite copper foil with good service life and electrical properties. Summary of the Invention

[0005] This invention aims to solve one or more technical problems existing in the prior art, and at least provide a beneficial alternative or create conditions. This invention provides a composite copper foil in which the first copper layer, the metal modification layer, and the base film have good bonding energy, and the second copper layer has good growth quality, resulting in a composite copper foil with good service life and electrical properties.

[0006] The inventive concept of this invention is as follows: This invention uses an amorphous thin film as a metal modification layer. The amorphous metal thin film has no grain boundaries, low free volume, low internal stress, and isotropic properties. When combined with the first and second copper layers, it reduces the sheet resistance of the composite copper foil, giving it excellent electrical properties. Furthermore, the metal modification layer enhances the interfacial bonding energy between the base film and the first copper layer, as well as between the metal modification layer and the first copper layer, resulting in good adhesion between the first copper layer and the base film, thus extending the service life of the composite copper foil. In addition, because it does not contain a NiCr polycrystalline alloy layer, it reduces nickel contamination of the electroplating solution, improves the growth quality of the second copper layer, thereby enhancing the electrical properties of the composite copper foil and increasing the service life of the electroplating solution.

[0007] Therefore, a first aspect of the present invention provides a composite copper foil.

[0008] Specifically, a composite copper foil includes a base film, a metal modification layer, a first copper layer, and a second copper layer sequentially disposed on the upper surface of the base film; and a metal modification layer, a first copper layer, and a second copper layer sequentially disposed on the lower surface of the base film.

[0009] The metal modification layer is an amorphous thin film layer.

[0010] Preferably, the metal modification layer includes at least one of a metal and a metal oxide.

[0011] Preferably, the thickness of the metal modification layer is 27-55 nm.

[0012] More preferably, the thickness of the metal modification layer is 30-50 nm.

[0013] Preferably, the metal comprises component A, component B, and component C; component A comprises at least one of zirconium, niobium, and molybdenum; component B comprises at least one of titanium, chromium, and nickel; and component C comprises at least one of cobalt, copper, tungsten, and tantalum.

[0014] Specifically, selecting three or more metals can, on the one hand, increase the entropy value of the alloy film, which is conducive to the formation of an amorphous phase; on the other hand, the complementary atomic sizes of different metal elements are conducive to eliminating internal stress, and the formation of specific intermetallic compounds is more conducive to forming strong bonding energy with the polymer base film, thereby improving the adhesion of the copper seed layer.

[0015] Preferably, by mass percentage, the content of component A is 27-77%, the content of component C is 0.1-1.1%, and the balance is component B.

[0016] More preferably, the content of component A is 30-70% by mass percentage, the content of component C is 0.1-1%, and the balance is component B.

[0017] Preferably, the metal oxide comprises component D, component E, and component F; component D comprises at least one of hafnium oxide, aluminum oxide, zinc oxide, and tin oxide; component E comprises at least one of titanium oxide, chromium oxide, nickel oxide, and indium oxide; and component F comprises at least one of zirconium oxide, tungsten oxide, tantalum oxide, and cerium oxide.

[0018] Preferably, by mass percentage, the content of component D is 20-89%, the content of component E is 10-79%, and the balance is component F.

[0019] More preferably, by mass percentage, the content of component D is 20-79%, the content of component E is 20-79%, and the balance is component F.

[0020] Preferably, the base film includes any one of PET base film, PP base film, and PI base film.

[0021] Preferably, the first copper layer is a copper seed layer, and the second copper layer is an electroplated copper layer.

[0022] Specifically, the amorphous thin film layer possesses characteristics such as high packing density, low free volume, low internal stress, and isotropy, and lacks grain boundaries. After the copper seed layer is sputtered onto the amorphous thin film layer, it can effectively reduce the induction effect of the copper seed layer's crystal orientation, resulting in excellent deposition uniformity and consistency, and improving the crystal quality and conductivity of the copper seed layer. Furthermore, due to the poor polarity of the base film itself, it is difficult to form strong bonds with the crystalline copper seed layer. However, this invention sets a metal modification layer between the copper seed layer and the base film. The metal modification layer has an amorphous structure, and according to the principle of polarity, it can form strong nonpolar van der Waals forces with the base film, improving the interfacial bonding strength. Simultaneously, due to the low internal stress of the amorphous thin film layer, it also generates a large bonding energy with the copper seed layer, resulting in good interfacial bonding energy among the base film, the amorphous thin film layer, and the copper seed layer. Therefore, bonding between the copper seed layer and the base film through the amorphous thin film layer can improve the bonding strength between the base film and the copper seed layer, extending the service life of the composite copper foil.

[0023] Preferably, the thickness of the first copper layer is 8-70 nm.

[0024] More preferably, the thickness of the first copper layer is 10-60 nm.

[0025] Preferably, the thickness of the second copper layer is 800-1000 nm.

[0026] More preferably, the thickness of the second copper layer is 850-950 nm.

[0027] A second aspect of the present invention provides a method for preparing the composite copper foil described in the first aspect of the present invention.

[0028] Specifically, the method for preparing the composite copper foil includes the following steps:

[0029] The metal modification layer, the first copper layer, and the second copper layer are sequentially prepared on the upper and lower surfaces of the base film to obtain the composite copper foil.

[0030] Preferably, the metal modification layer and the first copper layer are prepared by sputtering; the second copper layer is prepared by electroplating.

[0031] Preferably, the sputtering includes magnetron sputtering.

[0032] Preferably, the sputtering power of the metal modification layer is 1-6KW, and the sputtering pressure of the metal modification layer is 0.25-0.70Pa.

[0033] More preferably, the sputtering power of the metal modification layer is 1.5-5.5KW, and the sputtering pressure of the metal modification layer is 0.30-0.65Pa.

[0034] Preferably, the sputtering power of the first copper layer is 1.6-2.4KW, and the sputtering pressure of the first copper layer is 0.50-0.70Pa.

[0035] More preferably, the sputtering power of the first copper layer is 1.8-2.2KW, and the sputtering pressure of the first copper layer is 0.55-0.65Pa.

[0036] More preferably, the sputtering power of the first copper layer is 2KW, and the sputtering pressure of the first copper layer is 0.6Pa.

[0037] Preferably, the second copper layer is prepared by electroplating.

[0038] Preferably, the electroplating current is 2-12A; more preferably, the electroplating current is 3-11A.

[0039] Preferably, the electroplating time is 8-12 seconds; more preferably, the electroplating time is 9-11 seconds.

[0040] Preferably, the electroplating solution used for electroplating includes a copper sulfate solution.

[0041] Preferably, the concentration of the copper sulfate solution is 100-200 g / L.

[0042] A third aspect of the present invention provides a current collector.

[0043] Specifically, the current collector includes the composite copper foil described in the first aspect of the present invention.

[0044] Preferably, the current collector is a negative electrode current collector.

[0045] A fourth aspect of the present invention provides a lithium battery.

[0046] Specifically, the lithium battery includes the current collector described in the third aspect of this invention.

[0047] Compared with the prior art, the beneficial effects of the technical solution provided by the present invention are as follows:

[0048] (1) The present invention uses an amorphous thin film as a metal modification layer. The amorphous metal thin film has no grain boundaries and has a low free volume and isotropy. When combined with the copper seed layer and the electroplated copper layer, it can reduce the sheet resistance of the composite copper foil and give it good electrical properties. On the other hand, the base film and the copper seed layer are bonded through the metal modification layer, so that the base film, the amorphous thin film layer and the copper seed layer all have good interfacial bonding energy, which can improve the bonding strength between the base film and the copper seed layer and extend the service life of the composite copper foil.

[0049] (2) The metal modification layer of the present invention has the characteristics of high filling density, low free volume and isotropic, and there is no grain boundary. After sputtering the copper seed crystal layer, it can effectively reduce the induction effect of the crystal orientation of the copper seed crystal layer, so that the copper seed crystal layer has excellent deposition uniformity and consistency, improve the crystal quality and conductivity of the copper seed crystal layer, and improve the conductivity of the composite copper foil.

[0050] (3) Since the present invention does not contain a NiCr polycrystalline alloy layer, it can reduce the contamination of the electroplating solution by nickel, improve the growth quality of the electroplated copper layer, and extend the service life of the electroplating solution, thus saving costs. Attached Figure Description

[0051] Figure 1 This is a schematic diagram of the composite copper foil structure in Embodiment 1 of the present invention;

[0052] Figure 2 These are X-ray diffraction patterns of the metal-modified layers in Examples 1-3 of the present invention;

[0053] Figure 3 The X-ray diffraction pattern of the adhesion layer in Comparative Example 3 of this invention is shown below.

[0054] Figure 4 This is a transmission electron microscope (TEM) image of the metal modification layer in Embodiment 1 of the present invention.

[0055] Figure 5 These are the appearance images after adhesion testing in Embodiment 2 and Comparative Example 2 of the present invention;

[0056] Figure 6These are the appearance images after adhesion testing of Embodiment 3 and Comparative Example 3 of the present invention.

[0057] in, Figure 1 In the diagram, 100 represents the PET base film, 200 represents the metal modification layer, 300 represents the copper seed crystal layer, and 400 represents the electroplated copper layer. Detailed Implementation

[0058] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.

[0059] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.

[0060] Example 1

[0061] A method for preparing composite copper foil includes the following steps:

[0062] (1) A 4.5 μm thick PET base film was fixed on a glass substrate. A 30 nm thick metal modification layer and a 50 nm thick pure copper seed layer were sputtered sequentially on the surface of the PET base film using a multi-metal target and a high-purity copper target. Then, an electroplated copper layer was prepared on the copper seed layer by electroplating. The specific formula of the multi-metal target for preparing the metal modification layer was as follows: by mass percentage, it included 59% Mo, 20% Ni, 20% Ti and 1% Ta; the sputtering power was 5 KW and the sputtering pressure was 0.5 Pa. The sputtering power of the pure copper target for preparing the copper seed layer was 2 KW and the sputtering pressure was 0.6 Pa. The electroplating solution was 10 g / L copper sulfate solution, the electroplating current was 10 A, the electroplating time was 10 s, and the thickness of the electroplated copper layer was 900 nm. The preparation of the metal modification layer, the copper seed layer and the electroplated copper layer on the surface of the PET base film was completed.

[0063] (2) Using the same process and parameters as in step (1), a metal modification layer, a copper seed layer and an electroplated copper layer are sequentially prepared on the lower surface of the PET base film to obtain a composite copper foil.

[0064] The structural schematic diagram of the composite copper foil in Embodiment 1 of the present invention is shown below. Figure 1 As shown.

[0065] Example 2

[0066] A method for preparing composite copper foil includes the following steps:

[0067] (1) A 4.5 μm thick PP base film was fixed on a glass substrate. A 30 nm thick metal modification layer and a 70 nm thick pure copper seed layer were sputtered sequentially on the surface of the PP base film using a multi-metal target and a high-purity copper target. Then, an electroplated copper layer was prepared on the copper seed layer by electroplating. The specific formula of the multi-metal target for preparing the metal modification layer was as follows: by mass percentage, it included 60% Mo, 20% Ti, 19.5% Nb, and 0.5% W, with a sputtering power of 1.8 kW and a sputtering pressure of 0.36 Pa. The sputtering power of the pure copper target for preparing the copper seed layer was 2 kW and the sputtering pressure was 0.6 Pa. The electroplating solution was copper sulfate solution, the electroplating current was 3 A, the electroplating time was 10 s, and the thickness of the electroplated copper layer was 900 nm. The preparation of the metal modification layer, the copper seed layer, and the electroplated copper layer on the surface of the PP base film was completed.

[0068] (2) Using the same process and parameters as in step (1), a metal modification layer, a copper seed layer and an electroplated copper layer are sequentially prepared on the lower surface of the PP base film to obtain a composite copper foil.

[0069] Example 3

[0070] A method for preparing composite copper foil includes the following steps:

[0071] (1) An 18 μm thick PI base film was fixed on a glass substrate. A 30 nm thick metal modification layer and a 70 nm thick pure copper seed layer were sputtered sequentially on the surface of the PI base film using a metal oxide target and a high-purity copper target. Then, an electroplated copper layer was prepared on the copper seed layer by electroplating. The specific formulation of the metal oxide target for preparing the metal modification layer was as follows: by mass percentage, it included 36.5% ZnO, 62.5% In2O3, and 1% Ta2O5, with a sputtering power of 2 kW and a sputtering pressure of 0.6 Pa. The sputtering power of the pure copper target for preparing the copper seed layer was 2 kW and the sputtering pressure was 0.6 Pa. The electroplating solution was copper sulfate solution, the electroplating current was 3 A, the electroplating time was 10 s, and the thickness of the electroplated copper layer was 900 nm. The preparation of the metal modification layer, the copper seed layer, and the electroplated copper layer on the surface of the PI base film was completed.

[0072] (2) Using the same process and parameters as in step (1), a metal modification layer, a copper seed layer and an electroplated copper layer are sequentially prepared on the lower surface of the PI base film to obtain a composite copper foil.

[0073] Comparative Example 1

[0074] The only difference between Comparative Example 1 and Example 1 is that Comparative Example 1 did not sputter a metal modification layer on the PET base film; otherwise, it was the same as Example 1.

[0075] Comparative Example 2

[0076] The only difference between Comparative Example 2 and Example 2 is that Comparative Example 2 uses a NiCr target to sputter a 30nm thick adhesion layer on a PP base film, while the rest is the same as Example 2.

[0077] Comparative Example 3

[0078] The only difference between Comparative Example 3 and Example 3 is that Comparative Example 3 uses a CrTi target to sputter a 30nm thick adhesion layer on a PI base film, while the rest is the same as Example 3.

[0079] Performance testing

[0080] 1. XRD Testing

[0081] XRD diffraction analysis was performed on the metal-modified layers prepared in Examples 1-3, and the results are as follows: Figure 2 As shown, XRD diffraction analysis was performed on the adhesion layer of Comparative Example 3, and the results are as follows. Figure 3 As shown. Among them, Figure 2 and Figure 3 The x-axis 2θ represents the diffraction angle, and the y-axis Intensity (arb.units) represents the diffraction intensity (in arbitrary units). From Figure 2 It can be seen that the metal-modified layers prepared in Examples 1-3 do not have obvious diffraction peaks and are amorphous, indicating that the metal-modified layers prepared in this invention are amorphous thin film layers. Figure 3 It can be seen that the adhesion layer of Comparative Example 3 shows obvious diffraction peaks, indicating that the adhesion layer obtained by sputtering CrTi target on PI film in Comparative Example 3 is a crystalline thin film layer.

[0082] 2. Microscopic observation of tissues using transmission electron microscopy

[0083] The metal-modified layer prepared in Example 1 was observed by transmission electron microscopy, and the results are as follows: Figure 4 As shown, where Figure 4 (a) is a transmission electron microscope (TEM) image of the metal-modified layer. Figure 4 In the diagram, (b) is the Fourier transform of the area within the box in (a). Figure 4 It can be seen that the metal modification layer is in an amorphous state.

[0084] 3. Sheet resistance test

[0085] Sheet resistance tests were performed on the composite copper foils prepared in Examples 1-3 and Comparative Examples 1-3. Five samples were tested in each group, and the test results are shown in Table 1.

[0086] The test method for sheet resistance shall be in accordance with ASTM F390-11.

[0087] Table 1: Sheet resistance of composite copper foils prepared in Examples 1-3 and Comparative Examples 1-3

[0088] Examples / Comparative Examples Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 Example 1 30mΩ / □ 32mΩ / □ 28mΩ / □ 28mΩ / □ 30mΩ / □ Example 2 38mΩ / □ 38mΩ / □ 35mΩ / □ 39mΩ / □ 37mΩ / □ Example 3 42mΩ / □ 39mΩ / □ 44mΩ / □ 38mΩ / □ 38mΩ / □ Comparative Example 1 93mΩ / □ 95mΩ / □ 95mΩ / □ 90mΩ / □ 99mΩ / □ Comparative Example 2 76mΩ / □ 79mΩ / □ 75mΩ / □ 73mΩ / □ 78mΩ / □ Comparative Example 3 55mΩ / □ 49mΩ / □ 57mΩ / □ 52mΩ / □ 47mΩ / □

[0089] The test results from the examples and comparative examples show that when a metal modification layer is included, the composite copper foil exhibits lower sheet resistance, better conductivity, and consequently, lower heat loss and a higher safety factor during operation. This is because the metal modification layer is amorphous with low surface energy. After sputtering the copper seed layer, it effectively induces a preferred orientation of the copper seed layer and promotes grain growth. This preferred grain orientation effectively reduces grain boundary scattering, increases electron migration rate, lowers the sheet resistance of the composite copper foil, improves conductivity, and enhances its electrical performance.

[0090] 4. Adhesion test

[0091] After sputtering the copper seed layer in Examples 1-3 and Comparative Examples 1-3, samples were taken and the adhesion between the copper seed layer and the base film was determined using the cross-cut adhesion test. Five samples were tested in each group, and the test results are shown in Table 2.

[0092] The adhesion test was conducted in accordance with ASTM D3359-97 standard.

[0093] Table 2: Adhesion test results of copper seed crystal layers to base films in Examples 1-3 and Comparative Examples 1-3

[0094]

[0095]

[0096] In addition, the appearance comparison images after adhesion tests of Example 2 and Comparative Example 2 are shown below. Figure 5 As shown; comparison images of the appearance after adhesion tests for Example 3 and Comparative Example 3 are shown. Figure 6 As shown. Among them, Figure 5 (a) and 5(b) are the appearance images after the adhesion test of Example 2 and Comparative Example 2, respectively; Figure 6 (a) and 6(b) are the appearance images after the adhesion test of Example 3 and Comparative Example 3, respectively.

[0097] From Table 2 and Figure 5-6It can be seen that samples 2 and 3 showed no detachment, while sample 2 of Comparative Example 2 showed detachment, and sample 3 of Comparative Example 3 showed no detachment. This indicates that the copper seed layer and the base film of the present invention have good adhesion, further demonstrating that sputtering a metal modification layer between the copper seed layer and the base film can improve the adhesion between them. This is because the metal modification layer is amorphous with low internal stress, allowing it to generate a large bonding energy with the polymer base film and the copper seed layer, thus improving the interfacial bonding force. Comparative Example 2 used a PP film, which has poor polarity and is difficult to form a strong bond with the crystalline metal crystal. The NiCr adhesion layer did not significantly improve the adhesion, and the sample detached after the adhesion test. In contrast, the metal modification layer of Example 2 is amorphous. According to the principle of polarity, it can form a stronger non-polar van der Waals force with the PP film, improving the interfacial bonding strength. Therefore, no detachment was observed after the test in Example 2. The substrate of Comparative Example 3 is PI, making the adhesion layer relatively easy to adhere. The metal modification layer in Example 3 of the present invention can achieve the same 5B adhesion as the crystalline alloy adhesion layer.

[0098] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A composite copper foil, characterized in that, The film includes a base film, a metal modification layer, a first copper layer, and a second copper layer sequentially disposed on the upper surface of the base film; and a metal modification layer, a first copper layer, and a second copper layer sequentially disposed on the lower surface of the base film. The metal modification layer is an amorphous thin film layer; The composition of the metal modification layer is selected from at least one of metals and metal oxides; The metal comprises component A, component B, and component C; component A comprises at least one of zirconium, niobium, and molybdenum; component B comprises at least one of titanium, chromium, and nickel; and component C comprises at least one of cobalt, copper, tungsten, and tantalum. The metal oxide includes components D, E, and F; component D includes at least one of hafnium oxide, aluminum oxide, zinc oxide, and tin oxide; component E includes at least one of titanium oxide, chromium oxide, nickel oxide, and indium oxide; and component F includes at least one of zirconium oxide, tungsten oxide, tantalum oxide, and cerium oxide.

2. The composite copper foil according to claim 1, characterized in that, The first copper layer is a copper seed layer, and the second copper layer is an electroplated copper layer.

3. The composite copper foil according to claim 1, characterized in that, The thickness of the metal modification layer is 27-55 nm; the thickness of the first copper layer is 8-70 nm; and the thickness of the second copper layer is 800-1000 nm.

4. The method for preparing the composite copper foil according to any one of claims 1-3, characterized in that, Includes the following steps: The metal modification layer, the first copper layer, and the second copper layer are sequentially prepared on the upper and lower surfaces of the base film to obtain the composite copper foil.

5. The preparation method according to claim 4, characterized in that, The metal modification layer and the first copper layer are prepared by sputtering; the second copper layer is prepared by electroplating.

6. A current collector, characterized in that, Includes the composite copper foil according to any one of claims 1-3.

7. A lithium battery, characterized in that, Includes the current collector as described in claim 6.

Citation Information

Patent Citations

  • Composite copper electroconductive film, preparation method thereof and metal wiring circuit

    CN103730190A

  • Preparation method and preparation system of composite copper foil for negative current collector of lithium battery

    CN116145093A